Risk factors associated with the outcomes of pediatric bacterial meningitis: a systematic review - Daniela Caldas Teixeira; Lilian Martins Oliveira Diniz; Nathalia Sernizon Guimarães; Henrique Morávia de Andrade Santos Moreira; César Caldas Teixeira; Roberta Maia de Castro Romanelli (Elsevier, 2020)
Objective: The aim of this study was to systematically review the literature and answer the following central question: "What are the risk factors associated with worse clinical outcomes of pediatric bacterial meningitis patients?" Methods: The articles were obtained through literary search using electronic bibliographic databases: Web of Science, Scopus, MEDLINE, and LILACS; they were selected using the international guideline outlined by the Preferred Reporting Items for Systematic Reviews and Meta-analysis Protocols. Results: The literature search identified 1,244 articles. After methodological screening, 17 studies were eligible for this systematic review. A total of 9,581 patients aged between 0 days and 18 years were evaluated in the included studies, and several plausible and important prognostic factors are proposed for prediction of poor outcomes after bacterial meningitis in childhood. Late diagnosis reduces the chances for a better evolution and reinforces the importance of a high diagnostic suspicion of meningitis, especially in febrile pictures with nonspecific symptomatology. S. pneumoniae as a causative pathogen was demonstrated to be related to clinical severity. Conclusions: Early prediction of an adverse outcome may help determine which children require more intensive or longer follow-up and may provide the physician with rationale for parental counseling about their child's prognosis in an early phase of the disease. Resumo: Objetivo: O objetivo deste estudo é revisar sistematicamente a literatura e responder à seguinte questão central: "Quais são os fatores de risco associados a piores desfechos clínicos de pacientes pediátricos com meningite bacteriana?". Métodos: Os artigos foram obtidos através de pesquisa bibliográfica, nas bases de dados eletrônicas Web of Science, Scopus, Medline e Lilacs, e selecionados com diretriz internacional delineada pela abordagem Prisma (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). Resultados: A pesquisa bibliográfica identificou 1.244 artigos. Após a triagem metodológica, 17 estudos foram considerados elegíveis para esta revisão sistemática. Foram avaliados 9.581 pacientes até 18 anos nos estudos incluídos e vários fatores prognósticos plausíveis e importantes são propostos para a previsão de desfechos piores após meningite bacteriana na infância. O diagnóstico tardio reduz as chances de uma melhor evolução e reforça a importância de uma alta suspeita diagnóstica de meningite, especialmente em quadros febris com sintomatologia inespecífica. S. pneumoniae como patógeno causador demonstrou estar relacionado à gravidade clínica. Conclusões: A previsão precoce de um desfecho clínico desfavorável pode ajudar a determinar quais crianças necessitam de uma abordagem mais invasiva ou seguimento mais prolongado e pode fornecer ao médico a justificativa para o aconselhamento dos pais sobre o prognóstico de seu filho em uma fase inicial da doença. Keywords: Mortality, Complications, Child, Pediatrics, Hospitalized child, Bacterial infection, Palavras-chave: Mortalidade, Complicações, Criança, Pediatria, Criança hospitalizada, Infecção bacteriana